Longer Breastfeeding in Infancy Decreases Systolic Hypertension Risk in Young Adults - Rak Karolina; Kornafel Danuta; Bronkowska Monika (Polish Journal of Food and Nutrition Sciences)
Many studies show that breastfeeding is associated with numerous direct and indirect health benefits for children in later life, although the relationship between breastfeeding and cardiovascular risk is still equivocal. The aim of this study was to investigate the relationship between duration of breastfeeding and cardiovascular risk in young adults. The cross-sectional study was conducted on a group of 128 volunteers (71 women and 57 men) at the age of 19 years. It consisted of a questionnaire, together with anthropometric and blood pressure measurements. It was demonstrated that 90.3% of the participants had been breastfed and the mean duration of breastfeeding was 8.8±7.6 months. Participants who were breastfed for longer than six months had a significantly lower systolic blood pressure than those breastfed for less than six months. Results of analyses were consistent for the female group, the male group and the combined group. The results suggest that breastfeeding for longer than six months decreases systolic hypertension risk in young adults. The promotion of breastfeeding may decrease the rate of cardiovascular disease and thus improve health status of the population.